Research on UMP Advance human resource administration and management effectiveness - Mohd Hanafiah, Ahmad; Hasnah, Haron; Panda, Sitansu
The effectiveness of HR practices are essential to create organizations that are more competent. In other words, organization performance is affected positively by the extent of HR practices developed in the organization. However, organizations who do not value the properly management of its HR cause the challenge of whether organization has the sufficient capacity and competency to improve in terms of effectiveness of HR practices. Lifelong learning institution in Malaysia was chosen to be a case of study where UMP Advanced was selected. The purpose of this study is to investigate the elements of HR effectiveness for service organization, then evaluate the effectiveness of HR practices in influencing UMP Advanced performance. Afterwards, to explore why UMP Advanced performance is influenced by specific HR practices. The research design of this study is sequential explanatory design. It consists of two different phases, first by quantitative method and then followed by qualitative method. Questionnaires used as the quantitative approach are adopted from previous study to measure HR practices effectiveness and organization performance. 33 questionnaires were distributed to all employees of UMP Advanced. Quantitative data collected were then analyzed. Then, focus group interviews as qualitative approach were conducted with several representatives of employees of UMP Advanced in different departments. Qualitative data collected were then analyzed and used to explain the quantitative findings. The quantitative findings shown only training and development has significant relationship with employee retention and financial performance. Afterwards, results obtained are further justified by qualitative findings. Most interviewees agreed that training and development is essential for the development of competencies and skills to perform better in the organization. This findings could provide a deeper knowledge to the top management on how to utilize HRM and take necessary actions to achieve better organization performance.